2022
DOI: 10.1017/s0959270922000387
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the breeding phenology of the endangered ‘a‘o (Newell’s Shearwater Puffinus newelli) on Kaua‘i to better focus conservation actions and management decisions

Abstract: Summary The ‘a‘o, or Newell’s Shearwater Puffinus newelli, is an endangered shearwater species endemic to the Hawaiian Islands, with 90% of the world population found on Kaua‘i. Understanding the breeding phenology of the species is vital for identifying key periods for colony management actions and the timing and exposure frequency to infrastructure threats such as powerline collisions and light attraction. We used a combination of direct burrow monitoring and remote cameras at multiple colonies between 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Further, adults tend to be less active at the colony during the full moon [12][13][14][15][16]. Together, these results suggest that nocturnal seabirds avoid fledging on nights when the moon is fuller [17], yet few studies have assessed this hypothesis [15,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Further, adults tend to be less active at the colony during the full moon [12][13][14][15][16]. Together, these results suggest that nocturnal seabirds avoid fledging on nights when the moon is fuller [17], yet few studies have assessed this hypothesis [15,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…To our best knowledge, fledging of cavity‐nesting seabirds is not correlated to the moon cycle. Since the first studies, several authors stated that Newell's shearwaters from cross‐fostered and natural colonies fledged irrespective of the moon phase (Byrd et al, 1984; Telfer et al, 1987), which has been recently corroborated by the use of camera traps (Raine et al, 2023). Preliminary data suggest that Leach's storm‐petrels Hydrobates leucorhous also fledge across the moon cycle (Miles et al, 2010) and a radar survey conducted near a Barau's petrel colony at Réunion Island very convincingly demonstrated that the number of fledglings detected was not influenced by moonlight (Gineste, 2016).…”
Section: Evidence and Support On Hypothesesmentioning
confidence: 97%
“…Evidence from rescue programs supports the hypothesis that increased moonlight reduces the attraction and disorientation of seabirds, consequently reducing fallout magnitude. In species with synchronized breeding cycles, most fledglings leave nests within a period of time that is shorter than one lunar cycle, for example, Cory's shearwater Calonectris borealis (Figure S1; Rodríguez & Rodríguez, 2009), Barau's petrels Pterodroma baraui and wedge‐tailed shearwaters Ardenna pacifica (Chevillon et al, 2022), short‐tailed shearwater Ardenna tenuirostris (Rodríguez et al, 2014), or Newell's shearwater Puffinus newelli (Ainley et al, 2001; Raine et al, 2023). When plotting the number of stranded fledglings per night against the rescue date, we observe clear differences in the rescue patterns and the magnitude of the fallout: full moon is linked to shifts in the peak fallout date by decreasing the number of fledglings grounded during full moon nights (Figure 1).…”
Section: Evidence and Support On Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation